Dari Ekologis sampai Perubahan Iklim: Letusan Gunung Krakatau dan Dampaknya di Selat Sunda Akhir Abad XIX - Ramanda, Aprido Juan; Romadona, Enjel Ibrahim (PT Inovasi Penelitian Terpadu, 2025)
This research examines the impact of the 1883 Krakatoa eruption on eclogy, climate, and society in teh Sunda Strait. Using an environmental historiografi approach, the study, analyzes teh event chronology, ecological changes, global cooling phenomena, and socio-economic consequences. Findings reveal that the eruption devastated local ecosystem, triggered a tsunami causing thousands of casualties, and resulted in global cooling with a temperature decrease of 0.5-1 derajat Celcius. Additionally, the eruption altered global weather patterns, disrupted the colonial economic system, and significantly contributed to the advancement of volcanology studies. These findings provide new insight into the complex interaction between natural disasters and socio- ecological changes, emphasizing their relevance for future volcanic disaster mitigation.